Presenting your lived experience of mental health issues to health professional students: Findings from rural and regional Australia. Issue 4 (4th July 2022) - McGarry, Denise; Anderson, Judith; Sweeger, Kathryn
Abstract : Background: Introduction of mental health service users and their family within undergraduate health profession courses has become routine in many curriculums. Few studies have explored the expectations and perceptions of such presenters. Objectives: This study reports the perceptions of nine carers and consumers in a regional Australian University. Design: A descriptive design was utilised. Participants were recruited via a consumer and carer support group. A semi-structured interview and thematic analysis of the data were used to generate themes. Findings: The analysis identified six common themes that addressed personal benefits, an imperative to increase the awareness of others, a desire to do something worthwhile, personal changing of perspectives, expectations of the presentation role and characteristics of the presenter. Several points of difference between presenters and non-presenters and issues relating to rural and regional settings were identified. Conclusions: These findings suggest that in rural and regional areas participation is more likely when life circumstances exhibit employment stability as some feel threatened by stigma. The theme of 'expectations' adds to current knowledge, with presenter's expectations often being exceeded in terms of student attitudes across different study programs.